Cost-effectiveness of urine-based tuberculosis screening in hospitalised patients with HIV in Africa: a microsimulation modelling study. Issue 2 (February 2019) - Reddy, Krishna P; Gupta-Wright, Ankur; Fielding, Katherine L; Costantini, Sydney; Zheng, Amy; Corbett, Elizabeth L; Yu, Liyang; van Oosterhout, Joep J; Resch, Stephen C; Wilson, Douglas P; Horsburgh, C Robert; Wood, Robin; et al.
Summary: Background: Testing urine improves the number of tuberculosis diagnoses made among patients in hospital with HIV. In conjunction with the two-country randomised Rapid Urine-based Screening for Tuberculosis to Reduce AIDS-related Mortality in Hospitalised Patients in Africa (STAMP) trial, we used a microsimulation model to estimate the effects on clinical outcomes and the cost-effectiveness of adding urine-based tuberculosis screening to sputum screening for hospitalised patients with HIV. Methods: We compared two tuberculosis screening strategies used irrespective of symptoms among hospitalised patients with HIV in Malawi and South Africa: a GeneXpert assay (Cepheid, Sunnyvale, CA, USA) for Mycobacterium tuberculosis and rifampicin resistance (Xpert) in sputum samples (standard of care) versus sputum Xpert combined with a lateral flow assay for M tuberculosis lipoarabinomannan in urine (Determine TB-LAM Ag test, Abbott, Waltham, MA, USA [formerly Alere]; TB-LAM) and concentrated urine Xpert (intervention). A cohort of simulated patients was modelled using selected characteristics of participants, tuberculosis diagnostic yields, and use of hospital resources in the STAMP trial. We calibrated 2-month model outputs to the STAMP trial results and projected clinical and economic outcomes at 2 years, 5 years, and over a lifetime. We judged the intervention to be cost-effective if the incremental cost-effectiveness ratio (ICER) was less than US750/year of life saved (YLS) in Malawi and 940/YLS in South Africa. A modified intervention of adding only TB-LAM to the standard of care was also evaluated. We did a budget impact analysis of countrywide implementation of the intervention. Findings: The intervention increased life expectancy by 0·5–1·2 years and was cost-effective, with an ICER of 450/YLS in Malawi and 840/YLS in South Africa. The ICERs decreased over time. At lifetime horizon, the intervention remained cost-effective under nearly all modelled assumptions. The modified intervention was at least as cost-effective as the intervention (ICERs 420/YLS in Malawi and 810/YLS in South Africa). Over 5 years, the intervention would save around 51 000 years of life in Malawi and around 171 000 years of life in South Africa. Health-care expenditure for screened individuals was estimated to increase by 37 million (10·8%) and 261 million (2·8%), respectively. Interpretation: Urine-based tuberculosis screening of all hospitalised patients with HIV could increase life expectancy and be cost-effective in resource-limited settings. Urine TB-LAM is especially attractive because of high incremental diagnostic yield and low additional cost compared with sputum Xpert, making a compelling case for expanding its use to all hospitalised patients with HIV in areas with high HIV burden and endemic tuberculosis. Funding: UK Medical Research Council, UK Department for International Development, Wellcome Trust, US National Institutes of Health, Royal College of Physicians, Massachusetts General Hospital.